Risk Factors Associated with Multiple Recurrent Febrile Seizure in Childrenage 6 Month to 5 Years Old Presented with 1st Episode Febrile Seizure - Muangsawat, Kanphitcha; Mengwongwan, Nonthawat; Inmasom, Wanmaka (Health Science Clinical Research, 2024)
Objective: To identify risk factors associated with multiple recurrences of febrile seizures in children aged 6 months to 5 years who experienced their first febrile seizure. Methods: This retrospective cohort study followed patients from their first febrile seizure until the age of 5 years. The study included 561 children aged 6 months to 5 years who were diagnosed with their first febrile seizure at Uttaradit Hospital between August 8, 2011, and August 8, 2021. General information and clinical data were collected and analyzed using descriptive and analytical statistics, including continuous ratio for ordinal logistic regression, with both univariable and multivariable analyses. Results: The 405 patients who experienced their first febrile seizure, 13 patients (3.2%) had three or more recurrences, 11 patients (7.6%) had two recurrences, and 59 patients (14.6%) had one recurrence. The study found that the most significant risk factors for multiple febrile seizures were age ≤ 12 months (ORadj = 2.46, 95% CI = 1.631-3.728), a family history of epilepsy (ORadj = 2.43, 95%CI = 1.024-5.780), and mean corpuscular volume (MCV) <70 fL (ORadj = 1.55, 95% CI = 1.043-2.302). Conclusions: The analysis showed that the most significant risk factor for recurrent febrile seizures is experiencing the first febrile seizure at an age ≤12 months, followed by a family history of epilepsy and MCV <70 fL. It is recommended to develop treatment plans, preventive measures, and closely monitor patients at risk. Additionally, providing better counseling to parents about the likelihood of recurrence and educating them on proper care when their child has a fever or a seizure is crucial.